Evolution of networks from biological nets to the internet and WWW - Dorogovtsev S N; Mendes J F F (Oxford OUP, 2005)
This book is about the growth and structure of random networks. The principles of the complex organization and evolution of networks, natural and artificial, are the topic of this book.
Keywords: Computer network; Internet